Summation for m m and n n

Algebra Level 4

Let S ( n ) = k = 1 n ( 1 ) k + 1 k S(n) = \large\displaystyle \sum_{k=1}^n \left(-1\right)^{k+1} \cdot k

Find the total number of pairs of positive integer ( m , n ) (m,n) satisfying S ( m ) + S ( n ) + S ( m + n ) = 2011 S(m) + S(n) + S(m+n) = 2011


Try another problem on my new set! Warming Up and More Practice


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

From the first few n n , we note that

S ( n ) = ( 1 ) n + 1 n 2 = { n + 1 2 if n is odd. n 2 if n is even. \begin{aligned} S(n) & = (-1)^{n+1}\left \lceil \dfrac n2 \right \rceil = \begin{cases} \dfrac {n+1}2 & \text{if }n \text{ is odd.} \\ - \dfrac n2 & \text{if }n \text{ is even.} \end{cases} \end{aligned} .

And we can prove the claim is true for all n 1 n \ge 1 by induction (see Proof below).

Let us consider the three cases when m m and n n are both odd, both even and one odd, one even.

Case: both m m and n n are odd

S = S ( m ) + S ( n ) + S ( m + n ) Note that m + n is even. = m + 1 2 + n + 1 2 m + n 2 = 1 2011 \begin{aligned} \mathscr S & = S(m) + S(n) + S({\color{#3D99F6}m+n}) & \small \color{#3D99F6} \text{Note that }m+n \text{ is even.} \\ & = \frac {m+1}2 + \frac {n+1}2 - \frac {m+n}2 \\ & = \color{#D61F06}1 \ne 2011 \end{aligned}

Case: both m m and n n are even

S = S ( m ) + S ( n ) + S ( m + n ) Note that m + n is even. = m 2 n 2 m + n 2 = ( m + n ) 2011 \begin{aligned} \mathscr S & = S(m) + S(n) + S({\color{#3D99F6}m+n}) & \small \color{#3D99F6} \text{Note that }m+n \text{ is even.} \\ & = - \frac m2 - \frac n2 - \frac {m+n}2 \\ & = \color{#D61F06}-(m+n) \ne 2011 \end{aligned}

Case: m m is odd, n n one even

S = S ( m ) + S ( n ) + S ( m + n ) Note that m + n is odd. = m + 1 2 n 2 + m + n + 1 2 = m + 1 \begin{aligned} \mathscr S & = S(m) + S(n) + S({\color{#3D99F6}m+n}) & \small \color{#3D99F6} \text{Note that }m+n \text{ is odd.} \\ & = \frac {m+1}2 - \frac n2 + \frac {m+n+1}2 \\ & = m + 1 \end{aligned}

If S = 2011 \mathscr S = 2011 , then m + 1 = 2011 m + 1 = 2011 or m = 2010 m = 2010 , which contradicts the assumption that m m is odd. Therefore there is no solution.

Therefore, the total numbers of pairs of ( m , n ) (m,n) satisfying the equation is 0 \boxed{0} .


Proof:

  • For n n is odd: For n = 1 n=1 , S 1 = k = 1 1 ( 1 ) k + 1 k = 1 = 1 + 1 2 S_1 = \displaystyle \sum_{k=1}^1 (-1)^{k+1} k = 1 = \frac {1+1}2 , therefore, the claim is true for n = 1 n=1 .
  • Assuming the claim is true for n o d d n_{odd} , then

S ( n + 2 ) = k = 1 n + 2 ( 1 ) k + 1 k = S ( n ) ( n + 1 ) + ( n + 2 ) = n + 1 2 n 1 + n + 2 = ( n + 2 ) + 1 2 \begin{aligned} \qquad S({\color{#3D99F6}n+2}) & = \sum_{k=1}^{\color{#3D99F6}n+2} (-1)^{k+1} k \\ & = S(n) - (n+1) + (n+2) \\ & = \frac {n+1}2 - n-1 + n+2 \\ & = \frac {{\color{#3D99F6}(n+2)}+1}2 \end{aligned}

\quad Therefore the claim is true for n + 2 n+2 and is true for all odd n n .

  • For n n is even: For n = 2 n=2 , S 2 = k = 1 2 ( 1 ) k + 1 k = 1 2 = 1 = 2 2 S_2 = \displaystyle \sum_{k=1}^2 (-1)^{k+1} k = 1 - 2 = - 1 = - \frac 22 , therefore, the claim is true for n = 1 n=1 .
  • Assuming the claim is true for n e v e n n_{even} , then

S ( n + 2 ) = k = 1 n + 2 ( 1 ) k + 1 k = S ( n ) + ( n + 1 ) ( n + 2 ) = n 2 + n + 1 n 2 = ( n + 2 ) 2 \begin{aligned} \qquad S({\color{#3D99F6}n+2}) & = \sum_{k=1}^{\color{#3D99F6}n+2} (-1)^{k+1} k \\ & = S(n) + (n+1) - (n+2) \\ & = - \frac n2 + n +1 - n-2 \\ & = - \frac {\color{#3D99F6}(n+2)}2 \end{aligned}

\quad Therefore the claim is true for n + 2 n+2 and is true for all even n n .

  • Therefore, the claim is true for all n 1 n \ge 1 .

We've made the same solution, almost at the same time, sir!

Just one small correction, I believe that in the case in which both m m and n n are odd, the sum is 1 1 and not 0 0 .

Guilherme Niedu - 4 years, 1 month ago

Log in to reply

Thanks. I missed that.

Chew-Seong Cheong - 4 years, 1 month ago
Guilherme Niedu
May 4, 2017

S ( n ) = 1 2 + 3 4 + . . . + ( 1 ) n n \large \displaystyle S(n) = 1 - 2 + 3 - 4 + ... + (-1)^n \cdot n

S ( 1 ) = 1 , S ( 2 ) = 1 , S ( 3 ) = 2 , S ( 4 ) = 2... \large \displaystyle S(1) = 1, S(2) = -1, S(3) = 2, S(4) = -2...

S ( n ) = ( 1 ) n + 1 n 2 \color{#20A900} \boxed {\large \displaystyle S(n) = (-1)^{n+1} \cdot \left \lceil \frac{n}{2} \right \rceil }

If both m m and n n are even, m + n m+n will be also even. Then:

S ( m ) + S ( n ) + S ( m + n ) = n 2 m 2 n + m 2 \large \displaystyle S(m) + S(n) + S(m+n) = -\frac{n}{2} - \frac{m}{2} - \frac{n+m}{2}

S ( m ) + S ( n ) + S ( m + n ) = ( m + n ) \color{#20A900} \boxed {\large \displaystyle S(m) + S(n) + S(m+n) = -(m+n)}

Which will never be equal to 2011, since both m m and n n have to be positive

If both m m and n n are odd, m + n m+n will be even. Then:

S ( m ) + S ( n ) + S ( m + n ) = n + 1 2 + m + 1 2 m + n 2 \large \displaystyle S(m) + S(n) + S(m+n) = \frac{n+1}{2} + \frac{m+1}{2} - \frac{m+n}{2}

S ( m ) + S ( n ) + S ( m + n ) = 1 \color{#20A900} \boxed {\large \displaystyle S(m) + S(n) + S(m+n) = 1}

Which obviously will never be equal to 2011.

If one of them, say n n , is even, and the other, m m is odd, m + n m+n will be odd. Then:

S ( m ) + S ( n ) + S ( m + n ) = m + 1 2 n 2 + m + n + 1 2 \large \displaystyle S(m) + S(n) + S(m+n) = \frac{m+1}{2} - \frac{n}{2} + \frac{m+n+1}{2}

S ( m ) + S ( n ) + S ( m + n ) = m + 1 \color{#20A900} \boxed {\large \displaystyle S(m) + S(n) + S(m+n) = m+1}

Which will be equal to 2011 2011 for m m (the one set as odd) equal to 2010 \color{#20A900} \boxed {2010} , while n n (the one set as even) can take any value. But this is a contradiction, since m m has to be odd. So, the answer is 0 \color{#3D99F6} \boxed {\large \displaystyle 0} pairs.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...